Feasibility of Direct Vitrectomy-Sparing Subretinal Injection for Gene Delivery in Large Animals - Stranak, Zbynek; Ardan, Taras; Nemesh, Yaroslav; Toms, Maria; Toualbi, Lyes; Harbottle, Richard; Ellederova, Zdenka; Lytvynchuk, Lyubomyr; Petrovski, Goran; Motlik, Jan; Moosajee, Mariya; Kozak, Igor (Current eye research, 2024)
PURPOSE: To assess the safety and feasibility of direct vitrectomy-sparing subretinal injection for gene delivery in a large animal model. METHODS: The experimental Liběchov minipigs were used for subretinal delivery of a plasmid DNA vector (pS/MAR-CMV-copGFP) with cytomegalovirus (CMV) promoter, green fluorescent protein (GFP) reporter (copGFP) and a scaffold/matrix attachment region (S/MAR) sequence. The eyes were randomized to subretinal injection of the vector following pars plana vitrectomy (control group) or a direct injection without prior vitrectomy surgery (experimental group). Intra- and post-operative observations up to 30 days after surgery were compared. RESULTS: Six eyes of three mini-pigs underwent surgery for delivery into the subretinal space. Two eyes in the control group were operated with a classical approach (lens-sparing vitrectomy and posterior hyaloid detachment). The other four eyes in the experimental group were injected directly with a subretinal cannula without vitrectomy surgery. No adverse events, such as endophthalmitis, retinal detachment and intraocular pressure elevation were observed post-operatively. The eyes in the experimental group had both shorter surgical time and recovery while achieving the same surgical goal. CONCLUSIONS: This pilot study demonstrates that successful subretinal delivery of gene therapy vectors is achievable using a direct injection without prior vitrectomy surgery.
Keywords: Plasmids; zelené fluorescenční proteiny; Disease Models, Animal; zvířata; Genetic Vectors; prasata; Vitrectomy; Animals; pilotní projekty; modely nemocí na zvířatech; Gene Transfer Techniques; Swine, Miniature; plazmidy; Genetic Therapy; retina; Injections, Intraocular; Green Fluorescent Proteins; genetická terapie; studie proveditelnosti; Feasibility Studies; technika přenosu genů; vitrektomie; Swine; Pilot Projects; miniaturní prasata; Retina; injekce nitrooční; genetické vektory